Qualidade de vida relacionada à saúde de idosos institucionalizados: estudo multicêntrico dos fatores associados - Oliveira, Luiz Fabrício Santos de (2019)
Introduction: Elderly people living in long-term care facilities (LTC) often experience worse health conditions and report worse quality of life than noninstitutionalized elderly. Identifying the factors associated with the better quality of life of institutionalized elderly is relevant to offer better living conditions and dignity to this population. Objective: To verify the factors associated with the health-related quality of life of institutionalized elderly. Methodology: A multicenter cross-sectional study was conducted with 344 elderly residents in 7 ILP of João Pessoa-PB and 15 ILP of Piracicaba-SP. Six researchers interviewed the elderly who had cognitive ability to respond to the research instruments and perform the proposed physical exams. Validated questionnaires were used for assessment of cognitive status (Mini-Mental Examination State), physical (Katz and Fried scale) and nutritional (Mini-Nutritional Assessment). The oral health-related quality of life (HRQoL) was verified through the OHIP-14 (Oral Health Impact Profile) and GOHAI (Geriatric Oral Health Assessment Index) instruments. Overall health-related quality of life (HRQoL) was determined using the SF-12 (Short Form-12) instrument. In addition, body composition analysis was performed by Bioimpedance. Hand strength was assessed using a manual dynamometer. Oral health was assessed with regards dental caries experience and use and need of dentures, according to World Health Organization criteria, by two trained examiners (Kappa> 0.7). The swallowing threshold was evaluated according to the chewing cycle count with test food (3.7 g peanut). Spearman's correlation test was used to evaluate the interaction between the results of the OHIP-14 and GOHAI questionnaires. Data were statistically analyzed by Poisson multivariate regression models, with a 95% confidence interval. Results: The results of the study were reported in the form of two articles, which addressed the factors associated with HRQoL (1); and the factors associated with the HRQoL of institutionalized elderly (2). Article 1 - A strong correlation (p<0.001, r2 = -0.671) was observed between the results obtained (Mean ± SD) in the GOHAI (32.46 ± 3.85) and OHIP-14 (7.57 ± 8, 63). The factors associated with the greatest impact on oral health (highest OHIP score) were: being female, having healthy teeth, lower self-perception in general and oral health, as well as lower swallowing threshold (p<0,05). The variables associated with better quality of life (higher GOHAI score) were: higher number of filled teeth, better self-rated oral health and higher swallowing threshold (p<0,05). Article 2 - The SF-12 questionnaire presented an average score of 60.89 ± 14.50 points. Factors associated with the highest SF-12 score were: wandering, being non-fragile, not being malnourished, ingesting fewer drugs, having greater wrist strength and greater self-rated overall health (p<0,05). Conclusion: HRQOL is associated with better self-perception of oral health and higher swallowing threshold. HRQoL is associated with the physical and nutritional status of the elderly. Better quality of life is observed in independent elderly, with less health problems, with little or no influence of oral condition.